Experiments and numerical study on heat transfer of moist silica aerogel composites at high temperatures - Dong Li; Zhan-Wei Cao; Xiang-Qian Xie; Xin Chen; Ya-Ling He (Energy Storage and Saving, 2024)
Silica aerogel composites have promising applications in high-temperature heat storage insulation. However, the impact of high temperatures and moisture on their insulation performance remains unclear. To reveal the influences of high temperature and moisture absorption property on the heat transfer of silica aerogel composites, an experimental and numerical study was conducted to explore the micromorphology, thermophysical parameters, moisture absorption characteristics, and temperature response. The service temperature limit of the silica aerogel composite has been clarified. Measurements have conducted for the thermal conductivity, specific heat capacity, thermal diffusivity, specific surface area, density, porosity, and pore size distribution of the heated silica aerogel composite (at temperatures of 600, 800, 1,000, 1,100 and 1,200 °C). The moisture absorption characteristic curve at 20 °C has been obtained. Thermal testing of silica aerogel composites under varying heating temperatures and moisture content has been completed. Additionally, a numerical method has been developed to calculate the temperature curve of moist silica aerogel composites. The insulation performance of silica aerogel composite with varying moisture contents depends on the game between thermal conductivity and latent heat. Compared with the negative effect of the moisture content on insulation performance, the positive influence of moisture evaporation and heat absorption is dominant in situations involving temperatures higher than the phase transition temperature.